Analisis Hubungan Kualitas Permukiman Dengan Kondisi Kesehatan Masyarakat Di Kecamatan Kotagede Kota Yogyakarta Berdasarkan Sistem Informasi Geografis - Arfiani, Arfiani, Drs. H. Priyono, M.Si (2016)
Analysis of settlement quality relationships with public health conditions to find out the quality of the housing in the District Shareable Kotagede. Analyzing settlement quality relationships with public health in the District Kotagede. The method used in this study is a survey technique, with sampling purposive sampling. The analysis used the qualitative approach to GIS. Results obtained from this research is a map Shareable quality of the housing and settlement quality relationship analysis with the condition of the society. Shareable poor quality settlements along the river, good quality Shareable mostly located in the Village Rejowinangun and Shareable quality of the housing is in the midst District of Kotagede. The quality of mutual settlements with the conditions of the people have a relationship. Good quality of the housing has a high IR value measuring 0,617 Km2, quality of the housing being has a value of IR're measuring 0,537 Km2 and poor quality of the housing has a high IR value measuring 0,314Km2.